Auditory Evoked Potential Mismatch Negativity in Normal-Hearing Adults - Schwade,Laura Flach (2017)
Abstract Introduction Mismatch Negativity (MMN) corresponds to a response of the central auditory nervous system. Objective The objective of this study is to analyze MMN latencies and amplitudes in normal-hearing adults and compare the results between ears, gender and hand dominance. Methods This is a cross-sectional study. Forty subjects participated, 20 women and 20 men, aged 18 to 29 years and having normal auditory thresholds. A frequency of 1000Hz (standard stimuli) and 2000Hz (deviant stimuli) was used to evoked the MMN. Results Mean latencies in the right ear were 169.4ms and 175.3ms in the left ear, with mean amplitudes of 4.6μV in the right ear and 4.2μV in the left ear. There was no statistically significant difference between ears. The comparison of latencies between genders showed a statistically significant difference for the right ear, being higher in the men than in women. There was no significant statistical difference between ears for both right-handed and left-handed group. However, the results indicated that the latency of the right ear was significantly higher for the left handers than the right handers. We also found a significant result for the latency of the left ear, which was higher for the right handers. Conclusion It was possible to obtain references of values for the MMN. There are no differences in the MMN latencies and amplitudes between the ears. Regarding gender, the male group presented higher latencies in relation to the female group in the right ear. Some results indicate that there is a significant statistical difference of the MMN between right- and left-handed individuals.